Multivariable prediction of early malignancy detection among first-degree relatives of patients with hereditary colorectal cancer based on the health belief model: A cross-sectional study from the largest hereditary colorectal cancer cohort in China. - Liyuan Yang; Xiaojun Chen; Mengjiao Zhong; Zhiyong Pan; Xiaodan Wu (PLoS ONE)
Background First-degree relatives (FDRs) of hereditary colorectal cancer are at an increased risk of cancer and receiving early detection and surveillance on malignancies is an efficacious strategy to reduce cancer-related morbidity and mortality. But there is rare information on screening in this cancer high-risk group in China. Objective The aim of this study was to explore the detection and surveillance on malignancies and its predictors among FDRs of patients with hereditary CRC based on the largest hereditary colorectal cancer cohort from China. Methods We conducted an exploratory, descriptive, cross-sectional study. 530 FDRs were recruited from December 2021 to December 2022, evaluated using the questionnaire on knowledge, attitudes and behavior of malignancies early detection and the Champion's Health Belief Model Scale. The main outcome were identified using logistic regression analysis. Results Among all the FDRs, only 122 (23.0%) underwent malignancies early detection. The predictors of malignancies early detection included knowledge score (OR = 1.117, P < 0.001), sex (OR = 0.244, P < 0.001), age (OR = 4.627, P < 0.001), marital status (OR = 3.815, P < 0.001), chronic disease history (OR = 2.945, P < 0.01), diagnosis of index patient (OR = 2.876, P < 0.001), attitude about "cancer is preventable" (OR = 3.405, P < 0.05) and "one needs malignancies early detection even if feel healthy" (OR = 16.477, P < 0.001), perceived susceptibility (OR = 1.106, P < 0.05) and self-efficacy (OR = 1.244, P < 0.001). Conclusion The uptake of malignancy early detection among FDRs should be improved. Some demographic and health-related characteristics, knowledge score, perceived susceptibility and self-efficacy were the most important predictors of malignancies early detection. Enhancing the recognition of clinical features of hereditary CRC and offering personalized genetic counseling, along with tailored cancer risk assessments, could further optimize individual cancer surveillance and prevention strategies, helping to reduce the risk of malignancies in high-risk populations.